Antiplasmodial Evaluation of One Compound from Calophyllum flavoranulum - Jamilah Abbas; Syafruddin Syafruddin (Universitas Gadjah Mada, 2014)
Calophyllum flavoranulum (Clusiaceae family) is a big tree and medical plants from the tropical rain forest of the Indonesian continent. The organic extracts from stem bark yielded phenyl coumarin. The structure was elucidated with the aid of spectroscopic technique. Antiplasmodial activities of isolated compound was tested in vivo against Plasmodium berghei parasite and showed the best antiplasmodial activity. New flavoranulum coumarin compound showed activity against P. berghei parasite with inhibition growth 0, 31.33, 40, 30.67, 46 and 34% at dosage 1.1x10-10, 1.1x10-9, 1.1x10-8, 1.1x10-7, 1.1x10-6, and 1.1x10-5 mg/mL, respectively. Flavoranulum coumarin very active as antiplasmodial, and at 3 and 4 day incubation all of parasite were died.